Race and ethnicity the key concepts - Ansell, Amy Elizabeth 1964- (London Routledge/Taylor & Francis Group, 2013)
Situating the study of race and ethnicity within its historical and intellectual context, this much needed guide exposes students to the broad diversity of scholarship within the field. It provides a clear and succinct explanation of more than 70 key terms, their conceptual evolution over time, and the differing ways in which the concepts are deployed or remain pertinent in current debates. Fully cross-referenced and completed and complete with suggestions for further reading, Race and Ethnicity: The Key Concepts is an ideal resource for students of race, ethnicity, and nationalism. --Book Jacket.
Includes bibliographical references (pages 171-195) and index.
Keywords: Race; Race relations; Ethnicity; Ethnic groups